Determination of technological risk during maintenance work on oil tanks - Калиновський, Андрій Якович; Липовий, Володимир Олександрович; Титаренко, Андрій Вікторович (Technology audit and production reserves, 2015)
The article is devoted to the improvement of environmental safety at hazardous objects and surrounding areas with the presence of technological processes related to repair of oil tanks by controlling technological risks defined taking into account the influence of factors on their values. The aims of the study were man-made risks and extent of environment pollution as a result of accidents caused by process or the operation of the repair of oil tanks. In theoretical studies it was used complex of the methods: analytical - in the generalization of scientific advances on environmental safety and to identify ways to improve its effectiveness on dangerous objects and the surrounding areas with the process operation or repair of oil tanks; method of similarity theory and dimensional analysis - the study of hydro-mechanical cleaning tanks, as well as for determining the work of adhesion at the interface solid - liquid, and the study of layer formation of oil residues on the surfaces of the tank. In mathematical modeling of the formation of oil layer on the surface of the tank it was used the regression analysis of single and multi-factorial experimental curves. Experimental studies based on modern approaches of experimental design and methods of the theory of mathematical statistics. It was conducted mathematical modeling of harmful deposits formation on the internal surfaces of the walls of the tank, taking into account technological, physical and chemical properties of oil and gas-air temperature in it. It is experimentally verified and confirmed the adequacy of the proposed model. Calculation of the possible volumes of formation of environmentally hazardous products of cleaning storage tanks for oil and oil products to the content of harmful substances from manufacturing operations related to repair were conducted in view of the results of theoretical and experimental research.